Respon Pertumbuhan dan Hasil Tanaman Sawi Kailan (BrassicaeoleraceaeL.) Akibat Pemberian Berbagai Takaran Pupuk Bokasi Takaran Ayam - Rostian Nafery; Meriyanto Meriyanto; Indrawani Sinoem; Rika Fadhilah (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
This study aims to assess the response to growth and yield of kailan (Brassica oleraceae L.) due to various doses of chicken which was held on the land of the Faculty of Agriculture, University of Tridinanti Palembang on the island Semambu Village, Indralaya District, OganIlir Regency, South Sumatra Province from July 2020 to September 2020.The The factors studied were P0 = Control, P1 = 5 tons per hectare or the equivalent of 37.5 grams per planting hole, P2= 10 tons per hectare or the equivalent of 75 grams per planting hole, P3 = 15 tons per hectare or the equivalent of 112.5 grams per planting hole, P4 = 20 tons per hectare or the equivalent of 150 grams per planting hole, P5 = 25 tons per hectare or the equivalent of 187.5 grams per planting hole. Based on the research results obtained, conclusions can be drawn that the provision of chicken manure bokashi fertilizer at a rate of 15 tons per hectare or equivalent to 112.5 grams per planting hole (P3) give a good growth response and yield to the mustard kailan plant, which produces a plant height of 6 mst of 30.82 cm, the number of leaves 6 mst is 8.00, leaf area of 10.49 cm2, the root volume is 2.70 cm3, Wet plant weight of 10.06 g, top wet weight of 9.08 g, plant dry weight of 6.15 g.